2015
DOI: 10.1016/j.clinthera.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The Next Immune-Checkpoint Inhibitors: PD-1/PD-L1 Blockade in Melanoma

Abstract: Purpose Blocking the interaction between the programmed cell death (PD)-1 protein and one of its ligands, PD-L1, has been reported to have impressive antitumor responses. Therapeutics targeting this pathway are currently in clinical trials. Pembrolizumab and nivolumab are the first of this anti-PD-1 pathway family of checkpoint inhibitors to gain accelerated approval from the US Food and Drug Administration (FDA) for the treatment of ipilimumab-refractory melanoma. Nivolumab has been associated with improved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
405
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(417 citation statements)
references
References 85 publications
4
405
0
8
Order By: Relevance
“…PD-L1 expression on tumor cells is a suggestive, but inadequate, predictive biomarker of response to immune-checkpoint blockade (31), suggesting that PD-L1 expressed by other cells might also be a relevant target for therapy with these agents. It is conceivable that the blockade of PD-L1 on NK cells could be part of the mechanism of action of these Abs, through disruption of the regulatory interaction between NK cells and DCs, which could contribute to the more robust and efficient antitumor CD8 + T cell response seen with anti-PD-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 expression on tumor cells is a suggestive, but inadequate, predictive biomarker of response to immune-checkpoint blockade (31), suggesting that PD-L1 expressed by other cells might also be a relevant target for therapy with these agents. It is conceivable that the blockade of PD-L1 on NK cells could be part of the mechanism of action of these Abs, through disruption of the regulatory interaction between NK cells and DCs, which could contribute to the more robust and efficient antitumor CD8 + T cell response seen with anti-PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death ligand 1 (PD-L1), an inhibitory molecule frequently upregulated on tumor cells, is one of the major immunological checkpoints contributing to tumor-immune escape (28) through the inhibition of T cell activation and promotion of apoptosis of DCs (29) and CD8 + T cells (30). In several clinical trials, blockade of programmed death-1 (PD-1) or PD-L1 resulted in enhanced T cell function and improved immune-mediated tumor control (31). PD-L1 is expressed not only by tumor cells but also by tumor-infiltrating immune cells (32), and it has been shown that some patients with PD-L1 2 tumors can also respond to treatment (33).…”
mentioning
confidence: 99%
“…38,44 The extent to which "false negative" classification, due to heterogeneous expression in metastases, accounts for these observed responses is unclear. Further, the baseline levels of expression of PD-L1 by tumor cells or immune cells may have a prognostic value independent of the likelihood of response to therapy, and this needs to be clarified in order to understand how the baseline features may interact with the predictive value of the expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aberrant PD-L1 and PD-L2 expression by cancer cells has been reported in many human malignancies (17)(18)(19). A series of clinical trials concerning the systemic administration of therapeutic antibodies for blocking PD-1 or PD-L1 have shown a promising clinical effect in various tumors (20,21).…”
Section: Introductionmentioning
confidence: 99%